THE ROLE OF CIVIC ACTIVISM IN THE DEVELOPMENT OF MODERN CIVIL SOCIETY - Ikramjon Batirovich Masharipov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The scientific article explains that the main goal of modern civil society is to build a civil society with the help of citizens with a high level of civil activity. Citizenship is evident during the transition stages of the country's development. Even today, citizenship is gaining importance in various countries that are experiencing socio-political changes, or rather, are building a civil society. In order to understand the basis of civic activism, first of all, the problems of understanding the theoretical essence of citizenship were studied. In particular, the author's analytical comments on the possibilities of activating the development of citizenship and civic activity for civil society have been formed.